2008
DOI: 10.2147/ijn.s3234
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to titanium dioxide and other metallic oxide nanoparticles induces cytotoxicity on human neural cells and fibroblasts

Abstract: Abstract:The use of titanium dioxide (TiO 2 ) in various industrial applications (eg, production of paper, plastics, cosmetics, and paints) has been expanding thereby increasing the occupational and other environmental exposure of these nanoparticles to humans and other species. However, the health effects of exposure to TiO 2 nanoparticles have not been systematically assessed even though recent studies suggest that such exposure induces infl ammatory responses in lung tissue and cells. Because the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Besides, they also detected some degree of chromatin fragmentation, which was considered a sign of DNA damage. Another study reported impaired survival due to apoptosis and necrosis in both U87 cells derived from human astrocytic cell line and HFF-1 cells upon exposure to NPs (25 nm) for 48 h at doses as high as 100 μg/ml (Lai et al, 2008). Furthermore, BEAS-2B cells have been reported to undergo apoptosis, which was stimulated by caspase-3 cleavage and condensation of chromatin via ROS (Park et al, 2008).…”
Section: Studies With Cobalt Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, they also detected some degree of chromatin fragmentation, which was considered a sign of DNA damage. Another study reported impaired survival due to apoptosis and necrosis in both U87 cells derived from human astrocytic cell line and HFF-1 cells upon exposure to NPs (25 nm) for 48 h at doses as high as 100 μg/ml (Lai et al, 2008). Furthermore, BEAS-2B cells have been reported to undergo apoptosis, which was stimulated by caspase-3 cleavage and condensation of chromatin via ROS (Park et al, 2008).…”
Section: Studies With Cobalt Npsmentioning
confidence: 99%
“…NPs were found to have cytotoxic effects on human lung BEAS-2B cells and RAW 264.7 macrophages after an incubation period of 16 h at doses up to 50 μg/ml (Xia et al, 2008). Apart from causing ROS production, ZnO NPs were also reported to activate the JNK pathway (Lai et al, 2008).…”
Section: Studies With Zinc Oxide Nanowiresmentioning
confidence: 99%
“…The poor water solubility of titanium is often considered as an indicator of its biological inertness. However, studies and case reports of patients with malfunctioning titanium implants reveal a range of adverse effects associated with this metal, including inflammation [49], pain [8], cytotoxicity [50,51], metal allergy [52,53], genotoxicity [54], carcinogenicity [55] and implant failure [56]. The most widely researched effects of titanium are those on the bone cells-osteoblasts (bone-forming) and osteoclasts (bone-resorbing) [42,53,57,58].…”
Section: Adverse Effects Of Titanium Debrismentioning
confidence: 99%
“…Chromatin fragmentation was also reported, indicating possible DNA damage ( Figure 7). It was also found that both human neural astrocyte-like U87 cells and human fibroblast HFF-1 cells exposed to 25 nm TiO 2 NPs for 48 h had a decrease in cell survival for doses up to 100 μg/mL, with cell death reported as a combination of apoptosis and necrosis [81]. On the other hand, BEAS-2B cells underwent cell death Cellular uptake studies with 30 nm TiO 2 NPs have been carried out in human amnion epithelial WISH cells using transmission electron microscopy (TEM), with images showing most of the particles localized either inside vesicles or freely in the cytoplasm [85].…”
Section: Titanium Dioxide Nanoparticles and Nanowiresmentioning
confidence: 90%
“…Finally, ZnO NPs were found to reside in caveolae in the case of BEAS-2B cells, whereas in the RAW 264.7 cells, they resided inside lysosomes, with intracellular dissolution and release of Zn 2+ shown in both cases. In a different study, ZnO NPs also impaired the survival of human neural astrocyte-like U87 cells in a dose-dependent manner [81].…”
Section: Zinc Oxide Nanoparticles and Nanowiresmentioning
confidence: 96%